Accommodation Use and Academic Outcomes for College Students With Disabilities - Blasey, Julia; Wang, Cixin; Blasey, Ralph (Psychological reports, 2023)
Despite the availability of disability support services, college students with disabilities continue to face poorer academic outcomes than their peers without disabilities. The majority of eligible college students with disabilities do not register with their campus disability service to receive accommodations or supports. Among those who do utilize disability services, findings have been mixed regarding the relation between service use and students’ academic outcomes. Further, few studies have measured the use of disability services over time. The current study used secondary data to examine the relation between accommodation use and academic outcomes of undergraduate students with disabilities (N = 1980) who registered with the campus disability service during a 4-year study period. Descriptive findings for academic and accommodation use patterns are discussed with regard to gender, race/ethnicity, and disability type. Regression analyses showed that earlier registration with the disability service and longer duration of service use predicted more positive student outcomes, as measured by cumulative GPA and time to graduation. Continued accommodation use also positively predicted within-subject changes in students’ semester GPAs across the study period. However, services appear to be under-utilized, with 25% of participants only using accommodations for a single semester across the study period. This work has implications for improving service delivery within university disability offices to ensure students with disabilities can access needed supports in college.